2013
DOI: 10.1507/endocrj.ej12-0324
|View full text |Cite
|
Sign up to set email alerts
|

Short duration of diabetes and disuse of sulfonylurea have any association with insulin cessation of the patients with type 2 diabetes in a clinical setting in Japan (JDDM 30)

Abstract: Type 2 diabeTes melliTus (T2DM) is characterized by defects in both insulin secretion and action. The UK Prospective Diabetes Study has reported that β-cell function deteriorates progressively over time in patients with T2DM, irrespective of lifestyle and existing pharmacological intervention [1,2]. Consequently, insulin therapy is often required to achieve good glycemic control [3] and, in fact, in the clinical setting in Japan, outpatients with T2DM are started on insulin therapy. Conversely, protraction of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Arai et al . 16 found that the prevalence of sulfonylurea pretreatment is significantly lower in type 2 diabetes patients who were able to stop insulin therapy after transient insulin therapy than in those who were not able to stop insulin administration. Additionally, a longer duration of sulfonylurea treatment was associated with a decline in endogenous insulin secretion 17 .…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Arai et al . 16 found that the prevalence of sulfonylurea pretreatment is significantly lower in type 2 diabetes patients who were able to stop insulin therapy after transient insulin therapy than in those who were not able to stop insulin administration. Additionally, a longer duration of sulfonylurea treatment was associated with a decline in endogenous insulin secretion 17 .…”
Section: Discussionmentioning
confidence: 94%
“…Notably, patients with a lower postoperative CPI had a higher rate of sulfonylurea use before pancreatectomy. Arai et al 16 found that the prevalence of sulfonylurea pretreatment is significantly lower in type 2 diabetes patients who were able to stop insulin therapy after transient insulin therapy than in those who were not able to stop insulin administration. Additionally, a longer duration of sulfonylurea treatment was associated with a decline in endogenous insulin secretion 17 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, 185 of the participants (22.5%) were able to withdraw from insulin therapy within 12 months. The characteristics of that withdrawal group included short duration of diabetes and nonuse of insulin secretagogues such as sulfonylureas and glinides, the same factors as those observed in a previous study [17,18]. Insulin therapy would be expected to achieve "β-cell rest," which finally leads to the preservation and recovery of insulin secretory capacity in β-cells.…”
Section: Discussionmentioning
confidence: 99%
“…The patient profile across groups may have differed due to these unobserved factors or information unavailable in the database. For example, previous studies have reported that age at diagnosis, disease duration, and BMI were associated with clinical outcomes [ 7 , 21 ] and that disease duration and daily insulin dosage at the initiation were associated with insulin discontinuation [ 22 ]. We recommend careful interpretation of the current findings.…”
Section: Discussionmentioning
confidence: 99%